Metodologija interpretacije mladinske književnosti na Slovenskem - Haramija, Dragica (Slavistična revija, 2013)
This article presents the most important theoretical studies on Slovene children's literature. Taking into account the diversity of issues concerning literary history, literary theory, reception issues, and the didactics of literature, an overview of treatments of children's literature based on literary genres is most logical. There are many essays and commentaries on genres of poetry (e.g., by Niko Grafenauer, Igor Saksida, and Alenka Glazer). Narrative prose appears to be the most developed and diverse of the literary genres in this regard (e.g., Marjana Kobe, Igor Saksida, Metka Kordigel-Aberšek, Dragica Haramija, Milena Mileva Blažić), while children's drama is least discussed, including in book form (e.g., Igor Saksida, Vida Medved Udovič).
Keywords: history of literature; literarna zgodovina; literary history; methods; metodologija; raziskovanje; research; Slovene literature; Slovene youth literature; slovenska književnost; slovenska mladinska književnost